Luminescence theory and applications of rare earth activated phosphors - Tiwari, Ratnesh, 1982-; Dubey, Vikas, 1985-; Singh, Vijay; Zayas Saucedo, María Elena (De Gruyter, 2022)
"Phosphors are often consisting of transition-metal compounds or rare-earth compounds, with the most common application being displays and fluorescent light. This book will guide the reader through the latest developments in thermo-, electro-, mechano- and bioluminescence of rare earth phosphors and crystals. Also, the effect of doping will be discussed."--Publisher.